Police as communicators to prevent the spread of the COVID-19 - Anwar Sani; Suwandi Sumartias; Hanny Hafiar; Nurzali Ismail (Universitas Padjadjaran, 2022)
For the last two years, Indonesia and all countries in the world have been engaged with the COVID-19 pandemic. The government issued various forms of policies to prevent the spread of COVID-19, including PSBB and PPKM. The West Java Police Public Relations, as part of the government, also communicated the program through their social media. One of the social media accounts used is the Instagram account @humaspoldajabar. However, the uploaded content has yet to achieve optimal results. The purpose of this study is to describe the management of Instagram social media @humaspoldajabar during the COVID-19 pandemic. This research uses qualitative research methods with the type of case study research and collecting data using observation and literature study. The result of this research is that the contents uploaded by the Public Relations Division of the Java Regional Police are content related to appeals, information, and policies for controlling the COVID-19 outbreak. Public Relations of the West Java Regional Police uploaded content that described humanist police activities accompanied by the positive imagery of officials within the West Java Regional Police. The West Java Police Public Relations should use brand influencers to optimize content and display content that suits the needs and characteristics of the public. Content in the form of positive imagery can actually threaten the image of the police themselves.